Demographics, Clinical, and Microbiological Characteristics of Men with Urethritis in Cyprus - Hakan Evren; Emine Ünal Evren; Çetin Volkan Öztekin (Gazi Medical Journal)
Objective: Urethritis is a common sexually transmitted disease (STD) in developing countries; however, up to 40% of cases have no determined etiology. The characteristics of STDs vary geographically. This study aimed to define the demographic, clinical, and microbiological features of men with urethritis in Cyprus, where current data in the literature are lacking. Methods: We included 138 patients who sought care at a university hospital in Cyprus from 2017 to 2021 and had symptoms suggestive of urethritis or a history of a recent sexual partner with STD. Urethral swab samples of the patients were tested for seven pathogens (Trichomonas vaginalis, Neisseria gonorrhoeae (N. gonorrhoeae), Chlamydia trachomatis (C. trachomatis), Ureaplasma urealyticum (U. urealyticum), Ureaplasma parvum (U. parvum), Mycoplasma genitalium (M. genitalium), Mycoplasma hominis (M. hominis) by multiplex polymerase chain reaction assay. In addition, demographic, clinical, and microbiological data were obtained from the hospital program and analyzed. Results: Pathogens were detected in 59.4% of the cases: U. urealyticum in 26.8%, C. trachomatis in 13%, N. gonorrhoeae in 9.4%, U. parvum in 10.1%, M. genitalium in 10.1%, and M. hominis in 10.9%, with multiple microorganisms detected in 18.1%. Overall, 80.4% of the cases were symptomatic at presentation, and pathogen detection was associated with a history of STD, multiple sexual partners, and unprotected sexual intercourse. Conclusions: Urethritis is a common and heterogeneous clinical condition. U. urealyticum dominates male urethritis in Cyprus, yet many individuals have no detectable microorganisms. Future studies should focus on developing more comprehensive quantitative molecular diagnostic methods with determined cycle threshold values to shed light on the pathogenic roles of commensal microorganisms.